Comparison of theoretical and experimental analysis of P and Sn co-implantation in germanium - Mohamad Rashid, Nur Nadhirah (2017)
Ge is a promising candidate to replace Si since the Si downscaling is approaching its limit. Further optimization in ion implantation process parameters is required in order to fabricate highly activated n-type junction in Ge. The co-implantation technique is one of interest due to the enhanced active carrier concentration attributed to the stress associated with atomic size of the non-dopant. In this work, phosphorus (P) and tin (Sn) have been selected as dopant and non-dopant atoms for the co-implantation process. Theoretical analysis on dopant distribution in the substrate was performed using TRIM software. The calculation predicted a maximum concentration of n-type dopant up to 1E20 cm-3. Fabricated samples were then experimentally analyzed using SIMS for depth profiling. A difference of less than one order of magnitude was observed from the comparison of both results. The difference between TRIM and SIMS is attributed to the sputtering effect and the rise of temperature during co-implantation process.